Investigating the use of the ACTFL can-do statements in a self-assessment for student placement in an Intensive English Program. (February 2019) - Summers, Maria M.; Cox, Troy L.; McMurry, Benjamin L.; Dewey, Dan P.
Abstract: In this study, the authors use a validation framework to evaluate the usefulness of a self-assessment instrument based on the ACTFL Can-Do Statements for student placement in an Intensive English Program. The authors evaluated (a) the design of the instrument by investigating how well the intended item difficulties aligned with the actual item difficulties (ACTFL Proficiency Guidelines) and how well the scale functioned; (b) the assessment instrument itself through evaluating how reliably it distinguished between students with different levels of self-perception, and (c) the interpretation of scores that examined how well the results could be used as a proxy measure of student ability by comparing the students' perceived ability levels from the self-assessment instrument to their scores on speaking and writing placement tests. Results showed strong evidence for both the instrument's design and internal consistency; however, interpreting the scores as a measure of the students' productive skills was problematic. The correlations between self-assessment and placement test results were weak, raising questions regarding the use of this self-assessment in lieu of other placement measures.